Real-world pharmacogenetics of statin intolerance: effects of SLCO1B1, ABCG2, and CYP2C9 variants - Lönnberg K. Ivar; Tornio Aleksi; Hirvensalo Päivi; Keskitalo Jenni; Mustaniemi Anna-Liina; Kiiski Johanna I.; Filppula Anne M.; Niemi Mikko (LIPPINCOTT WILLIAMS & WILKINS, 2025)
Objective
The association of SLCO1B1 c.521T>C with simvastatin-induced muscle toxicity is well characterized. However, different statins are subject to metabolism and transport also by other proteins exhibiting clinically meaningful genetic variation. Our aim was to investigate associations of SLCO1B1 c.521T>C with intolerance to atorvastatin, fluvastatin, pravastatin, rosuvastatin, or simvastatin, those of ABCG2 c.421C>A with intolerance to atorvastatin, fluvastatin, or rosuvastatin, and that of CYP2C9*2 and *3 alleles with intolerance to fluvastatin.
Methods
We studied the associations of these variants with statin intolerance in 2042 patients initiating statin therapy by combining genetic data from samples from the Helsinki Biobank to clinical chemistry and statin purchase data.
Results
We confirmed the association of SLCO1B1 c.521C/C genotype with simvastatin intolerance both by using phenotype of switching initial statin to another as a marker of statin intolerance [hazard ratio (HR) 1.88, 95% confidence interval (CI) 1.08–3.25, P = 0.025] and statin switching along with creatine kinase measurement (HR 5.44, 95% CI 1.49–19.9, P = 0.011). No significant association was observed with atorvastatin and rosuvastatin. The sample sizes for fluvastatin and pravastatin were relatively small, but SLCO1B1 c.521T>C carriers had an increased risk of pravastatin intolerance defined by statin switching when compared to homozygous reference T/T genotype (HR 2.11, 95% CI 1.01–4.39, P = 0.047).
Conclusion
The current results can inform pharmacogenetic statin prescribing guidelines and show feasibility for the methodology to be used in larger future studies.